The Foot Musculature of the Rhesus Monkey (Macaca mulatta): An Anatomical Study - Christophe Casteleyn; Max Bosmans; Sofie Muylle; Jaco Bakker (Anatomia)
The rhesus monkey (Macaca mulatta) is a non-human primate with a genome that is 93.5% identical to that of humans. Both species, therefore, have numerous phenotypical similarities in common. Consequently, this non-human primate is regularly studied in biomedical research. Not only does the rhesus monkey play an important role as an animal model for studying human disease, but it is also often featured in zoos, and there are substantial feral populations that live in Asia. Since they are exploited as research subjects, their appropriate housing and husbandry and the validation of obtained research data benefit from the comprehension of the rhesus monkey anatomy. Unexpectedly, the number of anatomical documents on the rhesus monkey are largely outnumbered by publications on the anatomy of domestic animals. In addition, the limited number of available anatomical books and atlases are, unfortunately, outdated, e.g., by presenting black-and-white photographs and using archaic nomenclature, or failing to cover the in-depth anatomy of various anatomical systems. Since state-of-the-art data on the rhesus monkey anatomy are requested by biomedical researchers and veterinarians responsible for the daily care of these captive animals, the present study describes the musculature of the foot of the rhesus monkey. It builds on a recently published manuscript on the topographical anatomy of the pelvic limb of this non-human primate. Full-color anatomical (stereomicroscopic) photographs are taken during layer-by-layer dissections of the feet of three rhesus monkeys. All the muscles, from the superficial to the deepest layer, are described using veterinary anatomical nomenclature and annotated on multipaneled figures. Although the foot musculature of the rhesus monkey largely parallels that of its human counterparts, the small number of dissimilarities should be recognized when extrapolating these research data. In addition, a solid understanding of the rhesus monkey anatomy by veterinarians can be valuable during medical interventions, such as surgery for foot injuries.